1999
DOI: 10.1007/s001340050879
|View full text |Cite
|
Sign up to set email alerts
|

Mechanical ventilation of patients on long-term oxygen therapy with acute exacerbations of chronic obstructive pulmonary disease: prognosis and cost-utility analysis

Abstract: Applying mechanical ventilation to COPD patients treated with long-term oxygen therapy carries a high mortality and cost. Factors significantly associated with mortality in the ICU were albumin and sodium concentrations and FEV1 in hospital and in the first year after discharge.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
18
1
2

Year Published

2003
2003
2009
2009

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 61 publications
(22 citation statements)
references
References 32 publications
1
18
1
2
Order By: Relevance
“…There was statistically significant difference (p<0.05). We found that the mortality rate was 42.9%, this result was higher than previous studies, [8,9,11,12,14,15] but in our study all of the patients had respiratory failure and had mechanical ventilation.…”
Section: Discussioncontrasting
confidence: 73%
See 4 more Smart Citations
“…There was statistically significant difference (p<0.05). We found that the mortality rate was 42.9%, this result was higher than previous studies, [8,9,11,12,14,15] but in our study all of the patients had respiratory failure and had mechanical ventilation.…”
Section: Discussioncontrasting
confidence: 73%
“…Añón et al [8] found that comorbid diseases were presented in 8 patients of 20 patients. Chen et al [10] demonstrated that 204 of 439 patients had respiratory failure, 153 had cor pulmonale, 123 had coronary artery disease, 231 had hypertension, 70 had cerebrovascular disease and 32 had renal failure.…”
Section: Discussionmentioning
confidence: 98%
See 3 more Smart Citations